Assessing Grewia optiva Rhizobacteria’s Potential as a Bioformulation to Stimulate Plant Development - , Neerja Rana; Monika,; , Arti Ghabru; , Shivani Chauhan; , Bandana Kumari (Archives of Current Research International, 2025)
Plant growth promoting rhizobacteria (PGPR) involves the utilization of large array of soil bacteria to improve yield and plant growth. The bio-fertilizer with plant growth promoting rhizobacteria (PGPR) is reported to influence the growth, yield, quality and nutrient uptake by a variety of mechanisms. PGPR are reported to synthesize phyto-hormones such as indole-3-acetic acid (IAA), volatile organic compounds, increased mineral nutrient solubilization, nitrogen fixation, making nutrients available for the plant, repression of soil borne pathogens by the production of hydrogen cyanide and siderophore. India is an agriculture dominated country having largest livestock population in the world. Apart from this, livestock rearing is one of the major occupations in India that provides manure, forms important source of food and cash income to million. This domestication requires fodder which comes from local land areas, nurseries or habitat around the domestication. Providing a good fodder value, quality is necessary for livelihood. One such tree is Grewia optiva which is a multipurpose tree from tiliaceae family widely used as fodder in Norther Himalayan regions. Various studies have documented the increased health and productivity of different plant species by the application of plant growth promoting rhizobacteria under both normal and stressed conditions. The plant-beneficial rhizobacteria may decrease the global dependence on hazardous agricultural chemicals which destabilize the agro-ecosystem. The present investigation was conducted with aim of isolating and identifying the bacterial isolates from rhizopheric soil of Grewia optiva on the basis of different agroclimatic zone of Himachal Pradesh and evaluate them for PGPR traits to increase fodder quality. A total of 99 bacterial isolates were isolated and screened out of which 23 isolates were positive for PGPR traits. The isolates which showed maximum activity were further tested for quantitative estimation of growth promoting traits. Among the 23 isolates two isolates HKD1 and HSD8 demonstrated best results. HKD1 showed maximum P- solubilization (74.40 µg/ml), siderophore (71.50 µg/ml) and IAA (68.76 µg/ml) whereas HSD8 showed maximum P-solubilization (70.60 µg/ml), siderophore (66.56 µg/ml) and IAA (65.76 µg/ml). These isolates were further identified on the basis of 16S rDNA gene sequence. The two isolates were identified as Leclercia adecarboxylata and Enterobacter ludwigii. These isolates were further screened for biocontrol activity against Fusarium oxysporum and Rhizoctonia solani and were able to inhibit their growth. On the basis of plant growth promoting traits, two isolates HKD1 and HSD8 were selected and applied as biofertilizers for growth promotion of G. optiva. The biofertilizer with 40% RDF significantly increased the shoot and root parameters as well as fodder parameters. The available NPK content of the soil was also improved with application of biofertilizer.